Decision-making in the European Union / John Peterson and Elizabeth Bomberg. - Peterson, John, 1958- (The European Union series, 1999)
Based on exhaustive and original research, this book provides a theoretically-grounded analysis of how the European Union makes decisions in seven major policy sectors.